ORGANIZATION OF MUSIC CULTURE LESSONS IN GENERAL SECONDARY SCHOOLS - Tursunov Hurshid Abduraimovich (Journal Park Publishing, 2024)
In this article, "The content and level of competence of music culture lessons in general secondary schools were studied and highlighted.
Keywords: Education and training, music culture, art, pedagogue, competence, integration.